2020
DOI: 10.24198/ijpst.v7i3.27210
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferation Assay of Essential Oil of Curcuma Rhizoma (Curcuma xanthorrhiza Roxb.) Against P388 Leukemia Cell

Abstract: Leukemia or blood cancer is a disease which marked by abnormal increasing of blood producer`s cells. Chemotherapies which used as anticancer have a many adverse effect and toxicity. The volatile oil of turmeric rhizome (Curcuma xanthorriza) contains sesquiterpene which has an pharmacological activity. The aimed of this research to assay the antiproliferation activity of volatile oil from curcuma rhizome to leukemia P388 cells using MTT (3-[4,5-dimethylthiazole-2-yl]-2,5-diphenyl tetrazolium bromide) method. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Most C. zanthorrhiza rhizomes contain various sesquiterpene derivatives, including alpha and beta turmerone derived from the essential oil. Various studies have shown that the essential oil content of the rhizomes is in the range of 7.3-29.5% on a dry weight basis (Musfiroh et al 2020). In addition to terpenoids and curcuminoids, 150 other compounds that are also known to be abundant in C. zanthorrhiza rhizomes are the sesquiterpene phenol xanthorrhizol compounds (32%); beta-curcumin (17%), zingiberene (13%) and beta bisabolol (3.5%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most C. zanthorrhiza rhizomes contain various sesquiterpene derivatives, including alpha and beta turmerone derived from the essential oil. Various studies have shown that the essential oil content of the rhizomes is in the range of 7.3-29.5% on a dry weight basis (Musfiroh et al 2020). In addition to terpenoids and curcuminoids, 150 other compounds that are also known to be abundant in C. zanthorrhiza rhizomes are the sesquiterpene phenol xanthorrhizol compounds (32%); beta-curcumin (17%), zingiberene (13%) and beta bisabolol (3.5%).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to terpenoids and curcuminoids, 150 other compounds that are also known to be abundant in C. zanthorrhiza rhizomes are the sesquiterpene phenol xanthorrhizol compounds (32%); beta-curcumin (17%), zingiberene (13%) and beta bisabolol (3.5%). Xanthorrhizol is the dominant compound from the sesquiterpene group of C. zanthorrhiza that has pharmacological activity against cancer cell metastatic activity and for inhibition of tumor cells (Musfiroh et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Javanese turmeric (Curcuma xanthorrhiza Roxb) contains major metabolites such as curcuminoid, terpenoid, and xanthorrhizol essential oil that affect human organs, such as the gallbladder, liver, pancreas, rheumatism, stomach disease, and skin inflammation (Musfiroh et al, 2013). Xanthorrhizol from Curcuma xanthorrhiza Roxb has been reported as having antimicrobrial activity for S.aureus resistance (Kesumayadi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%